High field magnetic resonance imaging anatomy of feline carpal ligaments is comparable to plastinated specimen anatomy. Issue 5 (17th July 2018) - Basa, Rachel M.; Podadera, Juan M.; Burland, Gavin; Johnson, Kenneth A.
Abstract: Feline carpal ligament injuries are often diagnosed indirectly using palpation and stress radiography to detect whether there is instability and widening of joint spaces. There are currently no reports describing normal feline carpal ligament anatomy and the magnetic resonance imaging (MRI) appearance of the carpal ligaments. The objective of this prospective, anatomic study was to describe normal feline carpal ligament anatomy using gross plastinated specimens and MRI. We hypothesized that MRI could be used to identify the carpal ligaments as previously described in the dog, and to identify species specific variations in the cat. The study was conducted using feline cadaver antebrachii that were radiographed prior to study inclusion. Three limbs were selected for MRI to confirm repeatability of anatomy between cats. The proton density weighted pulse sequence was used and images were acquired in transverse, dorsal, and sagittal planes. Following MRI, the limbs were plastinated and a collagen stain was used to aid in identification of carpal ligament anatomy. These limbs were sliced in sagittal section, and a further six paired limbs were included in the study and sliced in transverse and dorsal planes. Anatomic structures were initially described using MRI and then subjectively compared with gross plastinated specimens. Readers considered the transverse MRI plane to be most useful for visualizing the majority of the carpal ligaments. Findings indicated that MRI anatomy of the carpal ligaments was comparable to plastinated anatomy; therefore MRI appears to be a beneficial imaging modality for exploration of feline carpal pathology.